Mindfulness Therapy Training: Efforts to Improve Mental Health of the Elderly in the Elderly Of Pimpinan Daerah Aisyiyah Banyumas Organization - Herdian Herdian; Ratna Estria, Suci; Setyawati, Rr; Sari Eka Dewi, Dinar (International Journal of Community Service Implementation, 2024)
This community service activity aimed to assess the effectiveness of Spiritual Mindfulness Therapy in enhancing the mental health of elderly individuals within a religious community setting. The activity involved 20 elderly participants from the Pengajian Pimpinan Daerah Aisyiyah Banyumas group and employed a pre-test post-test design to evaluate changes in mental health status. The participants' mental health was assessed using the SCL-90 instrument before and after the intervention. The intervention included a series of Spiritual Mindfulness Therapy sessions comprising lectures, focus group discussions, and practical mindfulness exercises. Demographic analysis revealed that the average age of the participants was 67.05 years (SD = 4.82), with education levels ranging from elementary school to university degrees. The results showed a significant reduction in SCL-90 scores, with the mean score decreasing from 185.75 (SD = 19.83) before the intervention to 146.90 (SD = 16.53) after the intervention. The Shapiro-Wilk test indicated a violation of the normality assumption (W = 0.88, p = 0.015), leading to the use of the Wilcoxon Signed-Rank Test for analysis. The test results were significant (W = 210.00, p < 0.001), demonstrating a substantial improvement in the participants' mental health following the intervention. These findings underscore the effectiveness of Spiritual Mindfulness Therapy as an intervention for improving mental health among the elderly, particularly in settings where spiritual practices are integral to daily life. This community service activity contributes to the ongoing efforts to enhance the well-being of older adults, suggesting that integrating spirituality into mindfulness practices can strengthen coping mechanisms and improve overall mental health.